The American Occupation Policy toward Japan 1945-1951 and Iraq 2003-2008: Comparative Historical Study (Journal of the College of Education for Women, 2019)
With their strategic and geographical positions, Japan and Iraq are one of the majorcountries in the world, especially to the United States. Japan lies near the two AmericanContinents, separated only by the Pacific and it is only normal to have the interests of bothcountries crossed and joined in the Far East region. This made the occupation of Japan aninventible matter in the second half of the 20th century. Iraq, on the other hand, has strategicposition in the Middle East, being surrounded by many active countries like Turkey, Iran, andGulf countries, besides Iraq’s oil wealth which is needed by such industrial country like theUnited States.